Pengembangan Branding Usaha Mikro, Kecil, Dan Menengah (UMKM) Bumbu Dapur Bu Siwin Dan Rahayu Wilujeng Telur Asin - Aulia Nida’ul Husna; Nur Rochmah Yulianita; Endang Iryanti (jurnal ABDIMAS Indonesia, 2023)
The MBKM Thematic Real Work Lecture (KKNT) organized by the East Java "Veteran" National Development University is a form of education by providing learning experiences for students to live in the community outside the campus, which directly together with the community identify potential and handle problems so that they are expected to be able to develop village/regional potential and concoct solutions to existing problems in the village. After observing Micro, Small and Medium Enterprises (MSMEs) in the District of Bareng, most of the Micro, Small and Medium Enterprises (MSMEs) do not have brand names on their products. This is a challenge for MBKM Thematic Real Work Lectures (KKNT) how to make Micro, Small and Medium Enterprises (MSMEs) in Bareng District have a brand on their products. The introduction of this product brand is useful for the progress of Micro, Small and Medium Enterprises (MSMEs) in the Bareng District in a modern way so that they are not left behind by other cities. With a work program that organizes branding and digital marketing in Bareng District, it can help Micro, Small and Medium Enterprises (MSMEs) to expand marketing, provide logos, packaging, and can assist in creating social media and e-commerce.